1990
DOI: 10.1021/la00098a016
|View full text |Cite
|
Sign up to set email alerts
|

Capillary condensation of xenon on exfoliated graphite

Abstract: Multilayer adsorptions of xenon on the loosely packed form and the strongly compressed form of exfoliated graphite were investigated by pressure-volume and X-ray diffraction techniques. The adsorption isotherm of Xe at 107 K on the loosely packed substrate showed four layering transitions, as well as the hysteresis loop between adsorption and desorption branches. From the measurement of X-ray diffraction at each stage of the adsorption, it was found that bulk crystallites of Xe started to appear just after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 0 publications
3
25
0
Order By: Relevance
“…The correlation length between the rows attains -1000 A, while that within the row is only -30 A. The row correlation length obtained is comparable to the surface coherence length of this substrate ( -500 A) [18]. This phase therefore can be viewed as a stack of onedimensional liquids.…”
mentioning
confidence: 58%
“…The correlation length between the rows attains -1000 A, while that within the row is only -30 A. The row correlation length obtained is comparable to the surface coherence length of this substrate ( -500 A) [18]. This phase therefore can be viewed as a stack of onedimensional liquids.…”
mentioning
confidence: 58%
“…However, experimental evidence supports the view that adsorption isotherms of ammonia [8,9], methane [10,11], carbon monoxide [12], krypton [13], xenon [14], acetone [15] and chloroform [16] on a graphite surface exhibit hysteresis at low enough temperatures. Hysteresis is normally only associated with mesoporous materials, resulting from the difference in the curvatures of the interface separating the adsorbed and gas phases along the adsorption and desorption branches of the isotherm.…”
Section: Introductionmentioning
confidence: 86%
“…These unusual hysteresis loops are observed at temperatures below the bulk triple point, and disappear as the temperature increases. In their study of Xe adsorbed on graphite, Morishige et al [14] attributed the hysteresis to capillary condensation in the confined spaces between micro-crystallites. Similarly, Kosugi et al [13], who observed hysteresis at temperatures in the range 86.91-120 K for krypton adsorbed on exfoliated graphite, attributed it to capillary condensation and to a liquid-solid phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…A powder-averaged Gaussian line shape [16] appropriate to the 2D structure was modified by the usual structure factor expression [17,18] taking into account the z component of the model structure. The profile parameters were used as determined previously on this substrate [19]. As Fig.…”
mentioning
confidence: 99%